Selected Shorts 1 a Pick from the Best Flemish Shorts of 2004 - Beels, Kaat; Meirhaeghe, Nele; Boswell, Douglas (Selected Shorts, 2005)
"Selected Shorts #1" offers 7 overwhelming Flemish short film productions from 2004, live-action as well as animation, professional productions as well as film school students' graduation projects. Featuring a.o. the widely acclaimed and awarded "Flatlife"! [www.kortfilmfestival.be]
Keywords: DVD-Video